PENDIDIKAN AFEKTIF DAN IMPLIKASINYA TERHADAP MODEL DAN DESAIN PEMBELAJARAN - Mufidah, Luk-luk Nur (State Islamic Institute of Madura, 2009)
This article describes the concept and theory of affective, as one of the education objectives domain inspite of cognitive and psichomotoric domains. Affective dimension is mainly connected to the development of emotional, moral, social, spiritual, esthetic, motivation. In fact, those three domains are lack of a proportional attention. National education practice focuses more on the cognitive aspect than effective aspect. The later aspect is considered prominent in preparing productive, mental health, honest, and independent generations. Consequently, it is urgent to optimalize the affective based education againts the moral decadent of the country. The effort of developing effective based education must be started by en effort of designing typical syllabus and learning that enables the educators to move freely to develop affective aspect.